Experimental evidence of size effect in nano-reinforced polymers: Case of silica reinforced PMMA. (December 2016) - Blivi, A.S.; Benhui, F.; Bai, J.; Kondo, D.; Bédoui, F.
Abstract: This study aims at quantifying the nano-size effect in terms of elastic and thermal properties in nano-reinforced polymers. Nano-reinforced PMMA with 4% volume fraction of silica nanoparticles was prepared using particle diameters of 15 nm, 25 nm, 60 nm, 150 nm and 500 nm. Uniaxial tensile tests showed an increase in Young's modulus with decreasing particle diameter when the volume fraction was kept constant. This increase is the signature of the nano-size effect on the macroscopic mechanical properties. Conversely to mechanical properties, the presence of particles in the matrix induced a decrease in glass transition, possibly due to weak interactions between the matrix and silica nanoparticles. Graphical abstract: